Determination Of Attitude Using Games And Purchase Intentions In E-Commerce - Hasna N. Khoirunnisa; Sumadi (Jurnal Manajemen, 2023)
This study aims to analyze the determinants of the use of games and the intention of buying in e-commerce. The data used is quantitative, with the population of Indonesian people who have played games in e-commerce. The data was collected using the nonprobability sampling method through the Google Form of 300 respondents. This study used Structural Equation Modeling (SEM) with the Lisrel version 8.80. To produce a fit model, this correlated study errors based on modification indices. Thus, the study concluded that utilitarian benefits and time/effort do not affect their attitude toward gaming use, but hedonic benefits and social values do affect their attitude toward gaming use, and the attitude toward gaming use has a positive effect on the intention of buying.